Path Analysis of the Relationship between Nutritional Status, Maternal Knowledge, Dietary Compliance and Health-Related Quality of Life in Children with Acute Lymphoblastic Leukemia - Arini Tri Lestari; Dewi, Yulia Lanti Retno; Salimo, Harsono; Hikmayani, Nur Hafidha (Journal of Maternal and Child Health, 2025)
Background: Acute Lymphoblastic Leukemia (ALL) is the most common type of blood cancer in children. Treatment for ALL may affect the patient's quality of life. Factors such as nutritional status, maternal knowledge of nutrition, and dietary compliance play a role in determining the quality of life of children with ALL. This study aims to analyze the relationship between nutritional status, maternal knowledge, and dietary compliance with health-related quality of life (HRQoL) in children with ALL. Subjects and Method: This study used a cross-sectional design with a sample of 52 children with ALL at the Pediatric Hematology Clinic of Dr. Moewardi Surakarta Hospital in October-November 2024. The independent variables were nutritional status, maternal knowledge, and dietary compliance, while the dependent variable was HRQoL. Data were collected using anthropometric instruments and questionnaires, then analyzed with single logistic regression and path analysis. Results: Single logistic regression analysis showed that nutritional status (OR= 4.60; 95% CI= 1.311 to 16.139; p = 0.017) and dietary compliance (OR= 4.82; 95% CI= 1.39 to 16.78; p= 0.013) were significantly associated with HRQoL. Maternal knowledge had no significant effect (OR= 1.88; 95% CI = 0.35 to 10.18; p = 0.467). Path analysis showed that nutritional status, dietary compliance, and body mass index had a direct positive association with the child's quality of life. The path analysis model showed a good fit with the data (goodness of fit p = 0.594). Conclusion: Nutritional status and dietary compliance are major factors in improving the quality of life of children with ALL. Although maternal knowledge does not have a direct effect, the mother's role remains important through improving the child's dietary compliance. Multidisciplinary interventions that integrate nutrition education and family support are needed to enhance HRQoL in pediatric patients with ALL.